Recent and Past Arboreal Change: Observational and Retrospective Studies Within a Subalpine Birch-Dominated (Betula Pubescens Ssp. Czerepanovii) Mountain Valley in the Southern Swedish Scandes - Responses to Climate Change and Land Use - Kullman, Leif; Öberg, Lisa (European Journal of Applied Sciences, 2022)
Multi-scale observations and reconstructions of treeline and associated plant cover changes are reviewed in this study. The main focus is on the dynamics of the treeline ecotone within a mountain valley in the southern Swedish Scandes. This area is well-researched for more than 100 years, with a background of historical studies covering the entire Holocene epoch. Trees were present on ice-free nunataks already during the Late-Glacial, 17 000-13 000 cal. a BP. Mountain birch (Betula pubescens ssp. czerepanovii), Norway spruce (Picea abies) and Scots pine (Pinus sylvestris) then grew 400-700 m higher than their current treelines, indicative of summer temperatures 3 °C higher than present. In addition, the tree flora contained Siberian larch (Larix sibirica) and broad-leaf thermophilic and deciduous species, Quercus robur, Corylus avellana, Ulmus glabra and Alnus glutinosa. Eventually, the climate turned cooler, particularly enhanced around 5000 cal. a BP. This course of change initiated the Neoglacial period, when thermophilic species were extirpated. Concomitantly, mountain birch forest and spruce benefitted from this course of change. Pine, on the other hand was disfavored and regressed in the treeline elevation and general abundance on the landscape. These trends continued until the Mediaeval period AD 1000-1300, when temperature raised above present-day standards and the pine treeline locally shifted upslope by at least 100 m. This favourable epoch was discontinued quite abruptly by resurgence of Neoglacial cooling; the “Little Ice Age”, which prevailed until the late 19th century. Widespread glacier expansion, high-elevation arboreal decline and treeline retraction then occurred. With a gentle onset in the late 19th century or somewhat earlier, a modern and still prevailing warming period was accentuated by the late 1930s. Subsequently, slight cooling prevailed for 3-4 decades, whereupon warming was resumed with short interruptions until the present day. One distinct short-term cooling-conditioned setback occurred during the 1980s. Transient permafrost formed close to the treeline, and locally some treeline recession took place. Thereafter, warming has re-occurred and glaciers and permafrost have receded. Treeline rise and densification of the treeline ecotone are once again active processes in the mountainscape. Currently, most conspicuous is a process of pine reclamation of local ground lost during the Little Ice Age. Hereabouts, seed regeneration, still virtually without winter injuries, is taking place at an unprecedented rate and abundance. Mountain birch is gaining ground in snow rich depressions in the birch belt and is currently regressing in exposed and snow-poor sections of the local topography. Current biotic changes within the treeline ecotone are well within the ranges of inferred natural variabilty during the postglacial period.